Composition of essential oil and antioxidant properties of Glaucosciadium cordifolium (Boiss.) B.L.Burtt and p.H.Davis Plant organs growing wild in Turkey - Maral, Hasan (Bangladesh Journal of Botany, 2022)
Glaucosciadium cordifolium is distributed in Central Anatolia, the Mediterranean region and Northern Cyprus. It has been used in traditional medicine as an aphrodisiac. In the present study the essential oil content, oil components and antioxidant properties of G. cordifolium plant collected from the natural location were determined. It was observed that the essential oil content and oil components obtained from fresh and dry plant parts differed. The highest essential oil ratio (1.40%) was obtained from the dried leaf, while the lowest ratio (0.15%) was obtained from the fresh stem. Analysis results showed that the main components of the essential oil were 1-phellandrene (9.23-34.08%), α-pinene (10.23-31.95%), dl-limonene (10.39-22.21%) and cis-ocimine (6.84-12.45%). In addition, some of these main components were higher in dry plant parts, while others were higher in fresh plant parts. In terms of antioxidant properties, higher values were obtained in dry plant parts as well as in the essential oil ratio. While the maximum radical scavenging activity values (32.70%) were obtained in the dry stem, the lowest value (16.63%) was obtained in fresh leaves. Bangladesh J. Bot. 51(3): 573-579, 2022 (September)